The Effectiveness of Acupressure for 3-Month Birth Control Acceptors Who Complaint of Menometrorrhagia - Winarti, Sri; Mukhodim Faridah Hanum, Sri; Rosyidah, Rafhani (Universitas Islam Lamongan, 2025)
The use of hormonal contraception, such as 3-month injectable birth control, is often associated with side effects of menstrual disorders, one of which is menometrorrhagia. Untreated menometrorrhagia can affect the quality of life of birth control acceptors. This study aims to evaluate the effectiveness of acupressure therapy in 3-month contraceptive injection acceptors who experience complaints of menometrorrhagia. The research used an experimental method with a posttest-only non-equivalent control group design. The sample consisted of 23 acceptors of 3-month contraceptive injections who were divided into two intervention groups: Intervention 1 (reducing complaints from moderate to mild) and Intervention 2 (reducing complaints from mild to very mild or cured). The intervention was carried out for 7 days, focusing on the SP6, LI4, LV3, CV3 and CV4 acupressure points with a duration of 15–20 seconds per point. The results of statistical analysis showed that the average rating of menometrorrhagia complaints in the Intervention 1 group (14.23) was higher than Intervention 2 (9.10) with a significant value (p = 0.029). This shows that there is a significant difference between the two intervention groups, where Intervention 1 is more effective in reducing complaints of menometrorrhagia. These findings indicate that acupressure therapy is an effective method and can be applied as a non-pharmacological alternative to treat menometrorrhagia in 3-month contraceptive injection acceptors.